2023
DOI: 10.1001/jamasurg.2022.7978
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Outcomes of Elective Parastomal Hernia Repair in Older Adults

Abstract: ImportanceParastomal hernia is a challenging complication following ostomy creation; however, the incidence and long-term outcomes after elective parastomal hernia repair are poorly characterized.ObjectiveTo describe the incidence and long-term outcomes after elective parastomal hernia repair.Design, Setting, and ParticipantsUsing 100% Medicare claims, a retrospective cohort study of adult patients who underwent elective parastomal hernia repair between January 1, 2007, and December 31, 2015, was performed. Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
(58 reference statements)
0
8
0
Order By: Relevance
“…We know that recurrence rates from PSH repairs are high, even in centres with a dedicated interest in PSH [14, 28]. This study will enable us to collect data on the operative techniques employed, including mesh usage, type, plane of placement and other technical factors, along with patient‐reported outcomes which will allow us to explore potential associations between operative techniques and patient‐reported outcomes including success rates, reintervention rates and QoL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We know that recurrence rates from PSH repairs are high, even in centres with a dedicated interest in PSH [14, 28]. This study will enable us to collect data on the operative techniques employed, including mesh usage, type, plane of placement and other technical factors, along with patient‐reported outcomes which will allow us to explore potential associations between operative techniques and patient‐reported outcomes including success rates, reintervention rates and QoL.…”
Section: Discussionmentioning
confidence: 99%
“…Up to one‐third of patients with a PSH will undergo a repair at some point and, of these, up to a third will undergo recurrent repairs [13]. A recently published retrospective cohort study from the USA found that 40.2% of patients had a complication from their PSH repair, with a cumulative 5‐year incidence of reoperation of 21.1% [14]. This reflects data from the Danish Registry which found a probability of 33% of recurrence requiring further surgery within 5 years [15].…”
Section: Introductionmentioning
confidence: 99%
“…For patients with a temporary ostomy who will become eligible for reversal, obesity is associated with both short-term complications as well as long-term hernia recurrence following parastomal hernia repair and ostomy reversal. 37,38 Again, insofar as patients can undergo ostomy takedown electively, it may be reasonable to consider referral for bariatric surgery preemptively to reduce the risk of postoperative complications and hernia recurrence.…”
Section: Benefits Of Preoperative Optimizationmentioning
confidence: 99%
“…Surgeons do not know the best way to repair a PSH, nor do they know whether watchful waiting is safe or whether it can result in more complications [2]. Additionally, recurrence risks from PSH repair are high [3,4].…”
Section: Introductionmentioning
confidence: 99%